Implementation of Integrated Dual Disorders Treatment: A Qualitative Analysis of Facilitators and Barriers - Brunette, Mary F; Asher, Dianne; Whitley, Rob; Lutz, Wilma J; Wieder, Barbara L; Jones, Amanda M; McHugo, Gregory J (Psychiatric services (Washington, D.C.), 2008)
Objective: Approximately half of the people who have serious mental illnesses experience a co-occurring substance use disorder at some point in their lifetime. Integrated dual disorders treatment, a program to treat persons with co-occurring disorders, improves outcomes but is not widely available in public mental health settings. This report describes the extent to which this intervention was implemented by 11 community mental health centers participating in a large study of practice implementation. Facilitators and barriers to implementation are described. Methods: Trained implementation monitors conducted regular site visits over two years. During visits, monitors interviewed key informants, conducted ethnographic observations of implementation efforts, and assessed fidelity to the practice model. These data were coded and used as a basis for detailed site reports summarizing implementation processes. The authors reviewed the reports and distilled the three top facilitators and barriers for each site. The most prominent cross-site facilitators and barriers were identified. Results: Two sites reached high fidelity, six sites reached moderate fidelity, and three sites remained at low fidelity over the two years. Prominent facilitators and barriers to implementation with moderate to high fidelity were administrative leadership, consultation and training, supervisor mastery and supervision, chronic staff turnover, and finances. Conclusions: Common facilitators and barriers to implementation of integrated dual disorders treatment emerged across sites. The results confirmed the importance of the use of the consultant-trainer in the model of implementation, as well as the need for intensive activities at multiple levels to facilitate implementation. Further research on service implementation is needed, including but not limited to clarifying strategies to overcome barriers. (Psychiatric Services 59:989-995, 2008)